Crepidomanes shenzhenense (subg. Crepidomanes; Hymenophyllaceae), a new filmy fern species from Guangdong, southern China - Wang, Hui; Zhao, Guo-Hua; Ravi, Baskaran Xavier; Lu, Shu-Gang (Phytotaxa, 2020)
A new filmy fern, Crepidomanes shenzhenense (Hymenophyllaceae) is described from Shenzhen, Guangdong, southern China. Crepidomanes shenzhenense is a tiny fern characterized by having a broadly obovate lamina only with internal false veinlets and crenate to dissected margins of involucre lips. The new species is presently known from two localities in Shenzhen. The distinctiveness between the new species and three relevatives, C. parvifolium, C. megistostomum and C. latealatum complex, are presented in detail.